Sekularisasi Seni Sakral: Refleksi Kritis Politik Kebudayaan Bali - Ida Bagus Gde Yudha Triguna; Anak Agung Inten Mayuni; Anak Agung Made Putra Arsana (Universitas Udayana, 2023)
The secularisation of sacred art in Bali is marked by its performances in various profane spaces and times. Local government regulations have not been able to overcome this problem. Therefore, this study aims to reflect critically on Balinese cultural politics in responding to the secularisation of sacred arts by applying qualitative methods. Data was collected through document studies, namely three policies related to strengthening and protecting sacred art in Bali and analysed using a critical policy analysis approach. This research found that the three policy documents were fragmentary in relation to other discourses. The regulation is also not implemented consistently, especially in relation to tourism. Based on this critical reflection, policies regarding sacred art in Bali need to be developed with a strategic and conceptual thinking (CST).